2022
DOI: 10.1111/jdv.18104
|View full text |Cite
|
Sign up to set email alerts
|

Value of pseudopod sign on high‐frequency ultrasound in predicting the pathological invasion of extramammary Paget's disease lesions

Abstract: Background Vertical invasion of extramammary Paget's disease (EMPD) is associated with poor prognosis. The usual vertical invasion route is directly downward or along the skin appendages. High-frequency ultrasound (HFUS) can be used to measure the EMPD lesion thickness, and visualize the pseudopod extensions due to skin appendage involvement. It is a non-invasive method for evaluating the extent of vertical invasion in EMPD. Objective To investigate the value of HFUS in predicting the extent of vertical invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The sensitivity, specificity, positive predictive value, and negative predictive value of high-risk pseudopodia in predicting invEMPD were 100, 84.7, 54.2, and 100%, respectively. 9 When skin biopsies of apocrine-rich areas from healthy volunteers were analyzed, it was seen that 19.4% of them presented skin appendages, which correlated sonographically with the presence of short strips in HFUS.…”
Section: Pseudopodsmentioning
confidence: 95%
See 4 more Smart Citations
“…The sensitivity, specificity, positive predictive value, and negative predictive value of high-risk pseudopodia in predicting invEMPD were 100, 84.7, 54.2, and 100%, respectively. 9 When skin biopsies of apocrine-rich areas from healthy volunteers were analyzed, it was seen that 19.4% of them presented skin appendages, which correlated sonographically with the presence of short strips in HFUS.…”
Section: Pseudopodsmentioning
confidence: 95%
“…Inflammation may cause slight overestimation to the EMPD thickness, as it is seen hypoechoic as well. 9 Affected Layer (Epidermis, Dermis, or Subcutaneous) Ma et al 8 and Chen et al 6 (n = 17) found that layer involvement using US and the pathological results were consistent in 85.0 and 88.2% of the lesions and inconsistent in 15.0 and 11.8%, leading to κ coefficient of 0.625 and 0.746, respectively. They both used UBM.…”
Section: Vertical Infiltrate Thicknessmentioning
confidence: 99%
See 3 more Smart Citations